3-D printing: adding a new dimension to intellectual property? - Khurshid, Z (2016)
3D printing is a phrase often seen in the media in relation to wondrous or troubling developments in manufacturing, health, arms and myriad other areas. The growth of 3D printing has the potential to have a major economic impact, and while we may be at a tilting point with regard to the relationship between 3D printing and intellectual property law, whether the future will see it as a truly ‘disruptive’ element remains to be seen.